Evaluation of the Effectiveness of P-SIGN Digital Signature Application Using Technology Acceptance Model (TAM) Approach at PT Pertamina Patra Niaga Regional South Sumatra - Ratna Juwita; Ahmad Syazili (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
This study analyzes how employees at PT Pertamina Patra Niaga Sumbagsel accept and use the P-SIGN digital signature platform through Technology Acceptance Model (TAM) analysis. Results show that P-SIGN usage aligns with Pertamina's digital transformation goals while supporting environmental initiatives by decreasing paper and ink consumption. Validity testing across variables X1, X2, X3, and Y1 confirmed all items as valid, with calculated r-values surpassing the table r-value (0.273). Reliability assessment yielded a Cronbach's Alpha of 0.821, demonstrating strong measurement consistency. The normality test produced an L-value of 0.220, exceeding the 0.05 significance threshold, verifying normal data distribution. While users generally responded favorably to P-SIGN, insufficient training created knowledge gaps about application features among certain staff members, potentially affecting their perception of usability. The study suggests strengthening internal education programs to maximize technology adoption rates across the organization